The Role Of Paper Quality And The Amount Of Water In Watercolor Painting (American Innovator: Journal of Emerging Technologies and Research, 2026)
This article analyzes, from both a scientific and a practical standpoint, the influence of two decisive factors in watercolor painting technique — the quality of the paper and the amount of water — on the final appearance of the work. Along with the paper’s weight (grammage), surface structure, method of manufacture, and water-absorption properties, the influence of the water-to-paint ratio on color saturation, layer transparency, and technical possibilities is examined in detail. The article consists of three main sections: the classification of paper, the technique of water quantity, and their combined influence. Each section presents practical recommendations, tables, and citations from scholarly sources.
Keywords: watercolor; paper grammage; paper surface